Effectiveness of Stunting Prevention Interventions Through MOCUGA Services Based on IEC (Information, Education, and Communication) Education Methods for Families - Putra, Yuda Ganda; Anriani, Nurul (Department of Public Administration, 2023)
Public knowledge about stunting prevention is correlated with the government's ability to provide health education services. The implementation of IEC Method through MOCUGA, which was initiated by Representatives BKKBN of Banten, is considered to increase public knowledge about stunting. This program, which is still considered premature, requires effectiveness measures that are output-oriented. Therefore, it is necessary to measure the effectiveness of MOCUGA intervention program for public knowledge level about stunting prevention. This research uses an experimental approach with a one group pre-test and post-test design. Data collection came from 95 respondents, selected from the population of Families at Risk of Stunting (KRS) in Sangiang Village, Lebak Regency of Banten Province. The collected data was analyzed using the t-test and Cohen's effect size method. It was found that 87.5% of mothers who had babies under two years old (Baduta), had the lowest level of knowledge about stunting prevention compared to other categories at the time of the pre-test. The level of very good knowledge about stunting prevention during the pre-test was determined by the prospective bride and groom (Catin) at 25%. Knowledge before and after the IEC education intervention through the MOCUGA program showed a difference of p = 0.034 and a correlation level of r = 0.397. However, the effectiveness of the MOCUGA intervention treatment is still classified as having a small effect of -0.22, on the impact of KRS knowledge about stunting prevention.